The Scalable Coherent Interface (SCI) as an Alternative for Cluster Interconnection - De Rose, César A. F.; Novaes, Reynaldo; Ferreto, Tiago; Oliveira, Fabio A. D. de; Barreto, Marcos E.; Ávila, Rafael B.; Navaux, Philippe O. A.; Heiss, Hans-Ulrich (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2001.22204, 2001)
The SCI standard was proposed in 1992 to be a high performance bus for processor interconnection in multicomputers. With the growing popularity of cluster architectures, the standard was implemented in PCI cards and of offered as a flexible an efficient alternative for the construction of parallel systems. After some initial difficulties, like incompatibilities with various PCI chipsets and the absence of drivers for some platforms, the SCl-based products are already mature but the expected breakthrough is not yet reached. In this paper we present our experience in the construction and utilisation of SCI clusters and in the development of support tools and applications for these systems. We present a survey of the obtained results over the last years in this area, including our own research, and make an analysis on how the standard and its implementations are performing today.